Prevalence of health related behaviors among rural community in Malaysia - Pasi, Hafizah; Md Isa, Zaleha; Shah, Shamsul Azhar (Japan International Cultural Exchange Foundation (JICEF), 2015)
Background: Health related behavior act as a gate to our health. Practicing good health related behavior will prevent us from contacting diseases especially of the non-communicable type, while engaging in poor health related behavior will increased the risk few folds. Objective: To determine the prevalence of health related behavior and its associated factors among the rural community in Malaysia. Methods: Cross sectional study on 520 residences aged 18 years and above from different ethnic and age group. Results: Respondents reported they engaged in physical activities for at least 3 times a week (39.5%), smoking at least 5 sticks cigarettes a day among male (52.2%) but mostly not smoking (99.4%) among female nor consumed any alcohol (99.6%). Most consumed fast food once a month (32.7%) and snacking between main meals for once per week (46.9%). The bi-variable analysis shows that factors which significantly associated with high risk health related behaviors were male, younger age, high level of education and female respondents with high body mass index. Conclusion: This study revealed that the prevalence of physically active is low while smoking among male respondents is high. Snacking is also high but comparable to other study conducted locally while fast food consumption is low. Thus, considering the importance of health related behaviors in improving health and preventing NCDs in this population, efforts need to be made to promote the good health related behavior in these settings.